Unusual Sound Sources - Jane Beethoven; Rosanne Emery; Cliff Lenz (Music magic video library, 1991)
Three distinct approaches to creating unusual music are explored. - - Take a trip to Bainbridge Island to discover a harp that plays only when the wind blows - - See how, through technology, animals can produce sounds that become the source for a musical composition - - Visit a junkyard with the Metaphonics and see how they work the sound properties of ordinary pieces of metal and wood into a most unusual performance.